2016
DOI: 10.1016/j.ijrobp.2015.12.269
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Study Evaluating Axitinib in Patients With Unresectable, Recurrent, or Metastatic Head and Neck Cancer

Abstract: In combination with IR, M3814 showed efficacy in all of the 6 mouse models of human cancer as demonstrated by a strong potentiation of the effect of IR. In all models, a dose of 2 Gy administered daily for 1 week in combination with M3814 induced statically significant tumor growth inhibition compared to IR alone. In 2 models, FaDu and NCI-H460, M3814 induced tumor regression. In the FaDu model, no tumor regrowth (duration of the experiment >100 days) was observed in the combination arm with IR (2 Gy per fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, antiangiogenic agents primarily targeting VEGF have disappointingly failed to demonstrate meaningful clinical activity in R/MSCCHN and can be associated with a risk of significant toxicity. Single‐agent phase 2 trials of oral multikinase VEGF receptor (VEGFR) inhibitors in R/MSCCHN have demonstrated low‐to‐modest antitumor activity (sorafenib: objective response rate [RR], 3.7%; disease control rate [DCR], 37%; sunitinib: RR, 2.6%; DCR, 50%; axitinib: RR, 0%; DCR, 77%; and no significant improvement in progression‐free survival [PFS]).…”
mentioning
confidence: 99%
“…However, antiangiogenic agents primarily targeting VEGF have disappointingly failed to demonstrate meaningful clinical activity in R/MSCCHN and can be associated with a risk of significant toxicity. Single‐agent phase 2 trials of oral multikinase VEGF receptor (VEGFR) inhibitors in R/MSCCHN have demonstrated low‐to‐modest antitumor activity (sorafenib: objective response rate [RR], 3.7%; disease control rate [DCR], 37%; sunitinib: RR, 2.6%; DCR, 50%; axitinib: RR, 0%; DCR, 77%; and no significant improvement in progression‐free survival [PFS]).…”
mentioning
confidence: 99%